Sociocultural factors, academic performance, and intercultural university education in the Peruvian Amazon - Morales Rocha, José Luis; Coyla Zela, Mario Aurelio; Serruto Medina, Genciana; Vargas Torres, Nakaday Irazema; Asencios Tarazona, Vitelio; Arroyo Japura, Gregorio; Huanca Frias, José Oscar (Frontiers in Education, 2024)
The educational context in the Peruvian Amazon is moderately complex because of the interaction between students from 23 indigenous peoples, with a preponderance of Shipibos-Conibos, Ashaninka, Awajun, Shawi, Yanesha, Wampis, Quechua, and Cacataibo, among the most representative and in that order, with culturally different knowledge and worldviews. Thus, the University becomes the center of tolerance, recognizing and accepting the identity of others and coexisting with mestizo students from urban areas. This study aims to determine the sociocultural and educational factors influencing academic performance in a virtual teaching context for intercultural university education in the Peruvian Amazon. A neural network model was applied to a sample of 162 students from a population of 1835 students at an intercultural university in the Peruvian Amazon. Further, 54% of the students are of mestizo origin and 46% belong to the indigenous population. It was concluded that economic dependence on the family, failing midterm exams, feeling isolated and alone, and conflicts with a family member influence academic performance. This is a provisional file, not the final typeset article significantly increased (Espinosa, 2017). Education in Peru has faced significant challenges in implementing and strengthening an accessible university education. Peru is a pluricultural and multilingual country because, in its geographic spaces, there are collectivities that possess a variety of cultures and languages (Rebaza & Seminario, 2018).Owing to the educational gaps in Peru, the government warned about the need to create intercultural universities to address comprehensive professional training. This will develop cultural extension activities in ethnolinguistic groups in the Peruvian Amazon and contribute to the preservation of indigenous culture in the context of plurality and sociocultural diversity, thereby indispensably guaranteeing the cultural identity of the progressive development of indigenous peoples. In Peru, there are 55 native people, 51 people belonging to the Amazonian area, and 4 people in the Andean area